A Study of Strength Activity Index of Pozzolan and Silica Sand with Ordinary Portland Cement Using ASTM C595 / C595M-12 Method - Susanti, Nova (Talenta Publisher, 2019)
Strength Activity Index (SAI) is a method that aims to see the quality of additional materials mixed into the cement. The additional materials examined in this study were pozzolan from Lubuk Alung, pozzolan from Sicincin, and silica sand from Payakumbuh. This study refers to the ASTM C595/C595M-12 standard. The process started with placing specimens and mold (on a base plate) in a humid room or closet and protecting the surface from water droplets. After the mold was removed from the humid room or closet, the cubes were removed from the mold. The cubes were placed in suitable metal or glass containers, and the containers were sealed and stored at a temperature of 38.0Â±2.00C for 27 days. The specimens were cooled to 23.0Â±2.00C before the tests were carried out. The compressive strength results of pozzolan from Lubuk Alung, pozzolan from Sicincin, and silica sand from Payakumbuh were 327 kgâ„cm2, 296 kgâ„cm2 and 199 kgâ„cm2 respectively. Thus, the specimens which fulfilled the SAI requirement according to ASTM C-618 were pozzolan from Lubuk Alung and pozzolan from Sicincin with 91.34% and 82.68%, respectively. In contrast, silica sand from Payakumbuh did not fulfill the requirement of ASTM C-618 at a minimum of 75% because the result obtained was only 55.58%.